2008
DOI: 10.1128/jvi.02642-07
|View full text |Cite
|
Sign up to set email alerts
|

NP, PB1, and PB2 Viral Genes Contribute to Altered Replication of H5N1 Avian Influenza Viruses in Chickens

Abstract: The virulence determinants for highly pathogenic avian influenza viruses (AIVs) are considered multigenic, although the best characterized virulence factor is the hemagglutinin (HA) cleavage site. The capability of influenza viruses to reassort gene segments is one potential way for new viruses to emerge with different virulence characteristics. To evaluate the role of other gene segments in virulence, we used reverse genetics to generate two H5N1 recombinant viruses with differing pathogenicity in chickens. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 63 publications
(65 reference statements)
2
71
0
Order By: Relevance
“…Overall, the emergence of an HPAIV may include these three preconditions: (i) the HA gene has to be prone to acquire a polybasic HACS (10,38), (ii) the acid stability of HA is complemented by the activity of M2 in pH reduction (29,31,39), and (iii) the other viral genes need to carry additional virulence and host range determinants (13,(40)(41)(42)(43)(44) like the NA stalk deletion (26)(27)(28). Those and other additional virulence determinants might be required to balance HA affinity with NA activity or to compensate potential inferior replication characteristics of such an evolving HPAIV.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the emergence of an HPAIV may include these three preconditions: (i) the HA gene has to be prone to acquire a polybasic HACS (10,38), (ii) the acid stability of HA is complemented by the activity of M2 in pH reduction (29,31,39), and (iii) the other viral genes need to carry additional virulence and host range determinants (13,(40)(41)(42)(43)(44) like the NA stalk deletion (26)(27)(28). Those and other additional virulence determinants might be required to balance HA affinity with NA activity or to compensate potential inferior replication characteristics of such an evolving HPAIV.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that infection with an HPAI virus results in upregulation of gene expression of gamma interferon (IFN-␥) and inducible nitric oxide synthase (58). However, the roles of proinflammatory cytokines in disease severity and outcomes in chickens infected systemically with HPAI viruses are largely unknown.…”
mentioning
confidence: 99%
“…Characterization of single-gene reassortants has led to a greater understanding of viral factors important for H5N1 virulence, particularly for the HA and PB2 proteins (3,10,15,31). More recently, the PB1-F2 protein has been shown to increase pathogenesis of the 1918 pandemic influenza virus and a recombinant virus bearing the PB1 segment of the A/Hong Kong/156/1997 (H5N1) virus.…”
mentioning
confidence: 99%